Postal Service and State Building: The Beginning of Postal Reforms in Chile (1840-1852) - de la Flor Pila, Rodrigo Pablo (2025)
This article reconstructs the process that led to Chilean postal reforms (1840-1852) and argues that their impetus resulted from the convergence of structural conditions (political peace, financial stability, and commercial boom) and an intellectual context favorable to "material progress." Drawing on official sources and ministerial reports, it traces how denunciations of the administrative obsolescence of the postal service and pressures from public and private actors (ministers, Valparaíso merchants, the press) grew from the late 1830s onward. It also examines the legislative projects of 1849-1850 (Urízar, congressional committee, Varas) and the dispute between privatization (through public tender) and a state-run model. The article argues that the presidential agency of Manuel Montt favored the state option that culminated in the Postal Rates Law of 1852 and subsequent ordinances. The study links concrete measures (prepayment, flat rate, adoption of stamps, expansion of offices) with processes of bureaucratization and increased "infrastructural power," and concludes that public ideas about the role of the state were decisive for the reform, providing evidence for the pacifist thesis on state building in Latin America.